Stabilizing the sternum using an absorbable copolymer plate after open surgery for pectus deformities: New techniques to stabilize the anterior chest wall after open surgery for pectus excavatum - (:unkn) unknown (My University, 2011)
An open surgical technique for the correction of pectus deformities using an absorbable copolymer plate for the sternal stabilization is described.